Back to the Origins: Background and Perspectives of Grapevine Domestication - Grassi, Fabrizio; De Lorenzis, Gabriella (International journal of molecular sciences, 2021)
Domestication is a process of selection driven by humans, transforming wild progenitors into domesticated crops. The grapevine (Vitis vinifera L.), besides being one of the most extensively cultivated fruit trees in the world, is also a fascinating subject for evolutionary studies. The domestication process started in the Near East and the varieties obtained were successively spread and cultivated in different areas. Whether the domestication occurred only once, or whether successive domestication events occurred independently, is a highly debated mystery. Moreover, introgression events, breeding and intense trade in the Mediterranean basin have followed, in the last thousands of years, obfuscating the genetic relationships. Although a succession of studies has been carried out to explore grapevine origin and different evolution models are proposed, an overview of the topic remains pending. We review here the findings obtained in the main phylogenetic and genomic studies proposed in the last two decades, to clarify the fundamental questions regarding where, when and how many times grapevine domestication took place. Finally, we argue that the realization of the pan-genome of grapes could be a useful resource to discover and track the changes which have occurred in the genomes and to improve our understanding about the domestication.